From the Dei Verbum to the 2008 Bishops’ Sinod on The Word of God - Pié-Ninot, Salvador (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
Prior to the Bishops’ Sinod on «The Word of God in the Life and Mission of the Church», this article aims to outline, as found in Dei Verbum, the essencial characteristics of the theology of the Word of God. The Word of God (Verbum) becomes God manifest for us, with an offer of historical salvation. This differs from Scripture (vox Verbi), which is the «testifying word» of the Word of God (H. U. Balthasar). The Word of God can be qualified as the «sacramental presence» of Christ by his «exterior sign» (sacramentum tantum), which is Scripture as the book and the text, by his «interior sign» (res et sacramentum), which is Scripture as «inspired» Book and interpreted by the Church, and as his «ultimate reality» (restantum), which is the «truth for our salvation» (DV 11), the ultimate purpose for the Word of God. The Word of God is discovered as «Scripture united to Tradition» (DV 21). It is precisely in the relationship of Tradition with the whole Church and the Magistery where there is a theogical vacuum that new and further studies should be able to fill.